MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MODEL PEMBELAJARAN COLABORATIVE LEARNING PADA MATA PELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH FAJRUL IMAN PATUMBAK DELI SERDANG - Wenaldi, Alan (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
This research is a Classroom Action Research which aims to improve students' motivation and learning outcomes of Arabic in the Collaborative Learning learning model in class VII Madrasah Tsanawiyah Fajrul Iman Patumbak Deli Serdang. The population in this study were all students of class VII, and the sample was 38 students. This research was conducted in 3 cycles. The instrument used in this study was a learning motivation questionnaire and an Arabic learning outcome test with a Collaborative Learning model. Data from the questionnaire and test results were analyzed quantitatively. The results showed that the data from the questionnaire results of student learning motivation towards Arabic learning, including the results of learning Arabic, had increased from cycle I to cycle II and cycle III. In the first cycle is in the medium criteria with a proportion of 66.7%. In the second cycle it increased by 14.9% to 81.6% with high criteria, in the third cycle it increased again by 6.4% to 88.0%. Students' Arabic learning outcomes have increased from cycle I to cycle II and to cycle III after learning with the Collaborative Learning model is implemented. This is shown by 38 students, the average test score has increased from 69.2 in cycle I to 80.7 in cycle II and increased to 87.8 in cycle III. Thus it can be said that the class has completed learning, because ≥ 85% of students have achieved learning completeness in the high category